2016
DOI: 10.3747/co.23.2998
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Costs of Intensity-Modulated and 3-Dimensional Conformal Radiotherapy in Ontario

Abstract: Background Radiotherapy is a common treatment for many cancers, but up-to-date estimates of the costs of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…The wide range of cost differential was affected by the time horizon of the cost analyses (eg, incorporating costs in the 12 mo since diagnosis [39] vs the lifetime of the patient after treatment [40]), health system of the country in which the study took place, whether or not the start-up phase of IMRT was incorporated, and the specific costs being measured (eg, Medicare reimbursements only [41] vs reimbursement costs along with the costs of equipment, supplies, personnel, and overhead [40]). The study with the lowest cost difference ($381) specifically assessed a mature IMRT program [42]. When it examined a scenario in which IMRT was in a start-up phase, the incremental cost of IMRT increased by a factor of 11 to $4268 [42].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of cost differential was affected by the time horizon of the cost analyses (eg, incorporating costs in the 12 mo since diagnosis [39] vs the lifetime of the patient after treatment [40]), health system of the country in which the study took place, whether or not the start-up phase of IMRT was incorporated, and the specific costs being measured (eg, Medicare reimbursements only [41] vs reimbursement costs along with the costs of equipment, supplies, personnel, and overhead [40]). The study with the lowest cost difference ($381) specifically assessed a mature IMRT program [42]. When it examined a scenario in which IMRT was in a start-up phase, the incremental cost of IMRT increased by a factor of 11 to $4268 [42].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The study with the lowest cost difference ($381) specifically assessed a mature IMRT program [42]. When it examined a scenario in which IMRT was in a start-up phase, the incremental cost of IMRT increased by a factor of 11 to $4268 [42]. Two studies found that IMRT costs less than 3D-CRT.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The dose deliver for patient in 3DCRT technique is easier than IMRT. It is also lower in cost and less time-consuming compared with IMRT [17] [18].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the cost of using new technologies needs to considered as if they only reduce toxicity profile due to treatment. In USA, systematic analysis of Medicare reimbursement data during 2012-2015, for prostate, anal, gynecological and headneck cancers, declared that IMRT has been more costly than 3DCRT approximately 12.834$ per patients and this cost can go up to 19.113$ and breast IMRT has been named as the least expensive IMRT depending on the less complex structure compared to a head and neck workload [43].…”
Section: Imrtmentioning
confidence: 99%